A Theory of Mind Based Programme for Enhancement of Children’s Social Skills - Babu, Nandita (INDIAN EDUCATIONAL REVIEW, 2012)
Theory of mind refers to the ability to attribute mental states to the self and others. This concept links up two very important areas of human development namely, cognitive and social. The quality of our relationships is affected by the extent to which we understand other people’s feelings, needs and motivation. Social insight and understanding of the social environment are often considered to be important abilities that underlie socially skilled behaviour. Aspects of relationships ranging from shared humour, to manipulation of control and power within a dyadic relationship, depend on a sophisticated grasp of others’ desires, needs, ideas and capacities.